Iron–copper interactions in iron‐limited phytoplankton in the northeast subarctic Pacific Ocean. (14th October 2015) - Semeniuk, David M.; Taylor, Rebecca L.; Bundy, Randelle M.; Johnson, W. Keith; Cullen, Jay T.; Robert, Marie; Barbeau, Katherine A.; Maldonado, Maria T.
Abstract: In August 2010, iron (Fe) and Fe and copper (Cu) addition incubation experiments were conducted at two low Fe stations (P20 and P26) along Line P, off the western coast of British Columbia, to investigate Cu physiology in Fe‐ and Fe‐light co‐limited phytoplankton. Chlorophyll a concentrations ([Chl a ]), maximum variable fluorescence yield ( F v / F m ), and Fe uptake rates by the Cu‐dependent high‐affinity Fe transport system (HAFeTS) were measured. Additions of Fe resulted in an increase in [Chl a ] and F v / F m at both stations compared with the controls, regardless of light availability, and confirmed that the phytoplankton communities were Fe‐limited. Uptake of Fe by the HAFeTS in both incubations increased with the addition of Fe, and likely reflects luxury Fe uptake and storage. While the in situ inorganic Cu concentrations were similar to those that can induce Cu‐limitation in laboratory cultures, increasing Cu availability had no effect on biomass accumulation during both incubations, regardless of Fe availability or light regime. At P26, additions of 1 nmol L −1 CuSO4 resulted in a short‐term increase in F v / F m of the phytoplankton community, and an increase in Fe uptake rates by large phytoplankton (>5 μm), but only when light was not limiting. These data confirm a complex interaction between light, Fe and Cu physiology in indigenous phytoplankton communities, and suggest that these interactions may be both spatially heterogeneous and different for different phytoplankton size classes.